Мировые загадки сегодня: научное издание / И. И. Адабашев - Адабашев Игорь Иванович (Сов. Россия, 1986)
Экземпляры: ФО-3 (20160610) / Инвентарный номер: 13525 / Сис.шифр: 20 / Авт.знак: А28 / ББК: 20В